Pandemic COVID-19 and Endemic Neglected Tropical Diseases: Friends or Foes? - Zarandi, Mehdi Borhani; Jin, Xuemin; Fathi, Saeid; Harandi, Majid Fasihi; Simsek, Sami; Ommati, Mohammad Mehdi; Ding, Jing (Compuscript Ltd, 2023)
The COVID-19 pandemic, caused by the SARS-CoV-2, is the most serious global health calamity since the 2nd World War. The COVID-19 pandemic threatens public health systems worldwide, both in developed and developing countries. In the present report we discuss various effects of the pandemic on the status of neglected tropical diseases (NTDs). COVID-19 will be a public health issue for an extended period. COVID-19 presented several challenges and opportunities for NTD prevention and control. Significant alterations include impact of the pandemic on preventive/control measures and poverty-related plans, service failures and injury to health workers, delayed treatment of NTDs, health service funding, and worsening poverty in marginalized societies. Additionally, the COVID-19 pandemic necessitated school and university closures on public education and research institutes. Furthermore, the COVID-19 pandemic has also provided opportunities, such as improving health literacy, changing approaches to NTD treatments, restructuring the health system and emergency responses, and enhancing science communication. © 2023 The Authors.
Keywords: COVID-19 pandemic; neglected tropical diseases; post-COVID-19 challenges